PENGARUH TOPOGRAFI LAHAN TERHADAP PRODUKTIVITAS KELAPA SAWIT (Elaeis guineensis Jacq.) DI PT. DHARMA INTISAWIT NUGRAHA MUARA WAHAU KABUPATEN KUTAI TIMUR - Humairo Aziza; Sri Ngapiyatun; Muhammad Arifin; Wartomo Wartomo; Rusli Anwar (Politeknik Pertanian Negeri Samarinda, 2021)
Oil palm is one of the potential commodities whose cultivation trend began in 2003 in EastKalimantan which has the characteristics of hilly land. Oil palm itself is preferable to grow at analtitude of 400 m asl with a slope of up to 23% or at 12°.Therefore, this research is motivated todetermine the yield of oil palm plantations in certain land slope classifications. The study wasconducted on 2 afdeling which have different land classifications with an area of ± 14,000 ha.Thenfor comparison, it was taken through production data in 2019 with 2 treatments and 12 replications,which were processed using Analysis Of Variance (ANOVA) Two Way Anova. Primary data wereobtained through field observations, as well as soil sampling, which were analyzed directly for soilphysical properties and laboratory for chemical properties including pH H2O, Nitrogen (N),Phosphorus (P), Potassium (K) and Magnesium (Mg.). The results of the research on the effect ofslope on oil palm production by various methods indicate that the land slope factor does not have asignificant effect on oil palm productivity.